Cdk5 mediates impaired autophagy by regulating NGF/Sirt1 axis to cause diabetic islet β cell damage - Tao, Yuejia; Liu, Yipeng; Hou, Shijie; Tang, Lijun; Wei, Kai; Zheng, Shanshan; Zhang, Ying; Wang, Zunsong; Liu, Shunyao (Frontiers in Cell and Developmental Biology, 2025)
The number of patients with diabetes is increasing annually, and islet β cell damage plays a central role in the occurrence and development of diabetes. The activation of cyclin-dependent kinase 5 (Cdk5) is involved in the development of diabetes; however, its specific mechanism has not been fully elucidated. This study aimed to investigate the role of Cdk5 in diabetic islet β cell injury. Our results indicate that Cdk5 is upregulated in islet β cells under diabetic conditions, which results in impaired autophagy, and that its inhibition mitites islet β cell injury. In addition, high glucose decreased the levels of nerve growth factor (NGF) and Sirtuin 1 (Sirt1). NGF knockdown was associated with Sirt1 downregulation, while its overexpression upregulated Sirt1, restored autophagy, indicating that NGF positively regulates Sirt1 in islet β cells. Finally, we found that the NGF inhibitor K252a attenuated the protective effect of Lv-Cdk5 shRNA against high glucose-induced islet β cell injury in a mouse model. In conclusion, Cdk5 negatively regulates the NGF/Sirt1 axis, resulting in impaired autophagy of islet β cells under high glucose environments, which lead to islet β cell dysfunction. The Cdk5-NGF/Sirt1 axis may be a new target for the treatment of diabetes.